TYPES OF BARRIER-MEMBRANE IN PERIODONTAL THERAPY OF GUIDED TISSUE REGENERATION - Diana Anton; Irina-Georgeta Sufaru; Maria-Alexandra Martu; Georgeta Laza Demirbuken; Raluca Mocanu; Silvia Martu (Romanian Dental Association for Education, 2019)
The present resorbable and non-absorbable membranes act as a physical barrier to prevent the fall of the connective and epithelial tissue in defect, favouring the regeneration of periodontal tissues. These conventional membranes have many structural, mechanical and biofunctional limitations. It is clear that the "ideal" membrane for use in periodontal regenerative therapy has not yet been developed. Based on a biomaterial-based approach, it was assumed that a biologically designed and functionally sized nanofibre material closely mimicking native ECM could succeed as the next generation of GTR / GBR membranes for periodontal tissue engineering.